2007
DOI: 10.1074/jbc.m609484200
|View full text |Cite
|
Sign up to set email alerts
|

Med19(Rox3) Regulates Intermodule Interactions in the Saccharomyces cerevisiae Mediator Complex

Abstract: The Saccharomyces cerevisiae Mediator is a 25-subunit complex that facilitates both transcriptional activation and repression. Structural and functional studies have divided Mediator subunits into four distinct modules. The Head, Middle, and Tail modules form the core functional Mediator complex, whereas a fourth, the Cyc-C module, is variably associated with the core. By purifying Mediator from a strain lacking the Med19(Rox3) subunit, we have found that a complex missing only the Med19(Rox3) subunit can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
57
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 41 publications
7
57
3
Order By: Relevance
“…Also consistent is the similar phenotype of med19-1002, given that Med19 has been implicated in stabilizing the association of the middle module with the rest of Mediator (Baidoobonso et al 2007). A caveat to the above is that our data do not formally rule out the possibility that the Mediator mutations affect mRNA stability instead of, or in addition to, transcription.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Also consistent is the similar phenotype of med19-1002, given that Med19 has been implicated in stabilizing the association of the middle module with the rest of Mediator (Baidoobonso et al 2007). A caveat to the above is that our data do not formally rule out the possibility that the Mediator mutations affect mRNA stability instead of, or in addition to, transcription.…”
Section: Discussionsupporting
confidence: 66%
“…The middle module confers structural integrity to Mediator (Baumli et al 2005). It also facilitates activated transcription in purified systems (Baidoobonso et al 2007) and has a dual role in both activation and repression in cells (Tabtiang and Herskowitz 1998;Gromoller and Lehming 2000;Singh et al 2006). The middle module also has been implicated in regulating transcriptional silencing (Zhu et al 2011a) and interaction with histone tails (Zhu et al 2011b).…”
mentioning
confidence: 99%
“…In addition, a fourth regulatory module comprising two Med subunits along with a cyclin-dependent kinase, Cdk8, and its associated cyclin, CycC, collectively called the kinase or Cdk8-cyclin C module, is also part of the Med complex. In contrast to the above model, Baidoobonso et al (2007) reported an intact and stable complex comprising only the tail and head modules without the middle module. Until recently, the metazoan Med complexes were known to share 22 Med subunits with S. cerevisiae , having eight subunits (Med23 to -30) unique to them.…”
contrasting
confidence: 60%
“…In addition to stimulating basal transcription, the Mediator complex plays a crucial role in the activation and repression of eukaryotic mRNA synthesis [11,12] . The Mediator complex, which consists of at least 20 subunits with multiple activities, including Rox3 (Med19), was first characterized through biochemical and genetic studies in Saccharomyces cerevisiae in the early 1990s [13,14] .…”
Section: Introductionmentioning
confidence: 99%